A Study Evaluating the Effectiveness of Social Media as a Marketing Tool For Events: A Case Study of EIB - Kwadzie, Theresa (UniMAC-GIJ, 2019)
The purpose of the study is to evaluate the effectiveness of social media as a marketing tool in the event management industry in Ghana by focusing on EIB. The study adopted the mixed method approach and sampled the views of 70 staff members with a questionnaire via the judgmental sampling method. Findings showed that all respondents agreed that the firm use social media to promote its events. The findings suggest that the reason for adopting the use of social media for event promotion is based on it being a new trend and more effective. On the issue of benefits of adopting the use of social media respondents extremely agreed that that social media increased brand awareness, increased brand loyalty ( cost-effectiveness and faster in reaching wider audience. Respondents agreed with the statement that social media created the platform for better customer satisfaction. The study concludes that in its bid use social media to promote and manage its event the organisation must consider all the possible problems that would come with it to deal with it ahead of time in order to stay competitive and ahead of its competitors. It was recommended that a team has to be set up equipped with the necessary information and know-how solely in charge of responding to comments, enquiries and questions on social media. Also, since social media sites can be exploited for the information it provides on consumer behaviour with regards to their purchasing intentions, research further suggests that businesses should incorporate social networking sites into their business model or promotional mix.
MA Media Management